Act of Mar. 11, 1911, ch. 90, 1911 Me. P. & S.L. 338, 338 (Amending "An Act for the Protection of Deer in York County"). - (:unkn) unknown (General Publisher, 1911)
It shall be unlawful to hunt deer with a shot gun in this county.
--
Keywords: HUNTING REGULATION